Aktivitas Antibakteri dan Penetapan Kadar Flavonoid Fraksi Daun Kalangkala (Litsea angulata) Serta Profil Kromatografi Lapis Tipis: Antibacterial Activity and Determination of Flavonoid Levels of Kalangkala Leaf Fraction (Litsea angulata) and Thin Layer Chromatography Profile - Rohama Rohama; Melviani Melviani; Rahmadani Rahmadani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Traditionally the people of Kalimantan use kalangkala (Litsea angulata) to treat various diseases, one of which is diarrhea. It is known that kalangkala contains flavonoids that have antibacterial activity. Kalangkala leaf extract was tested for antibacterial activity against Escherichia coli which is one of the bacteria that causes diarrhea by diffusion and dilution. Then flavonoid levels are determined by the Spectophotometry UV-Vis method and see how thin layer chromatography profiles at the fraction level to find out how much flavonoid compounds there are. The results showed that kalangkala leaf extract has antibacterial activity against E.coli by diffusion obtained the diameter of the inhibitory zone already visible at a concentration of 20 mg / ml. Dilutionally obtained the value of KHM at a concentration of 50% and KBM at a concentration of 100%. Flavonoid levels in the extract were 71,367 mg QE(Quercetin Equialen)/g, at the n-Hexane fraction of 8,367 mg QE(Quercetin Equialen)/g, at the ethyl acetate fraction of 6,700 mg QE(Quercetin Equialen)/g and at the aquadest fraction of 5,700 mg QE(Quercetin Equialen)/g. Profile of Thin-Layered Chromatogaphy of the n-Hexane fraction with n-Hexane : Ethyl Acetate (8:12) eluene appeared 7 stains, ethyl acetate fraction with ethyl acetate : N-Hexane (3:7) eluene appears 5 stains and aquadest fraction with butanol: acetic acid : aquadest (4:1:5) eluent appears 2 stains.